THE RELATIONSHIP OF CAREER MOTIVATION, PERCEIVED EDUCATIONAL COST BURDEN, AND STUDY DURATION WITH ACCOUNTING STUDENTS’ INTEREST IN PARTICIPATING IN PPAk - Resti Nur Insani; Yuli Novitasari; Miri Ardiansyah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study was motivated by the low interest of accounting students in participating in the Accounting Professional Education Program (PPAk), despite the program’s important role in developing professional accountants. This study aimed to analyze the influence of career motivation, perceived educational cost burden, and study duration on accounting students’ interest in enrolling in the PPAk program. This study employed a quantitative approach. The population consisted of 40 students from the Accounting Study Program at Universitas Sains Indonesia, cohorts 2021-2022, and a saturated sampling technique was applied. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 27. The results indicated that career motivation and study duration had a positive and significant effect on students’ interest in enrolling in PPAk, while perceived educational cost burden had a negative and significant effect. Simultaneously, career motivation, perceived educational cost burden, and study duration significantly influenced accounting students’ interest in participating in PPAk. These findings suggest that increasing students’ career motivation, managing study duration effectively, and implementing more affordable educational cost policies may enhance students’ interest in pursuing accounting professional education.